Dimer catastrophes and plasmid resolution - Summers, David (Henry Stewart Talks, 2008)
Multicopy plasmid inheritance, The causes of plasmid instability, Plasmid multimer formation and the dimer catastrophe, Plasmid dimer resolution by site-specific recombination, The Rcd checkpoint and its role in multicopy plasmid stability